2017
DOI: 10.1016/j.jconrel.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of loading concentration, blood and synovial fluid on antibiotic release and anti-biofilm activity of bone cement beads

Abstract: Antibiotic loaded cement beads are commonly used for the treatment of biofilm related orthopaedic periprosthetic infections; however the effects of antibiotic loading and exposure of beads to body fluids on release kinetics are unclear. The purpose of this study was to determine the effects of (i) antibiotic loading density (ii) loading amount (iii) material type and (iv) exposure to body fluids (blood or synovial fluid) on release kinetics and efficacy of antibiotics against planktonic and lawn biofilm bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Antibiotic loaded CS‐B are utilized as an augment to deliver locally high concentrations of antibiotics at periprosthetic infection sites. Previous studies have demonstrated the effectiveness of CS‐B as a carrier for antibiotics against a lawn of bacterial biofilm . Antibiotic loaded CS‐B reduced biofilms upto six log in the present study with a 24 h exposure period.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Antibiotic loaded CS‐B are utilized as an augment to deliver locally high concentrations of antibiotics at periprosthetic infection sites. Previous studies have demonstrated the effectiveness of CS‐B as a carrier for antibiotics against a lawn of bacterial biofilm . Antibiotic loaded CS‐B reduced biofilms upto six log in the present study with a 24 h exposure period.…”
Section: Discussionsupporting
confidence: 55%
“…Bioluminescent strains of S. aureus (SAP231, a transformed USA 300 MRSA strain) and a P. aeruginosa PAO1 derivative (Xen 41, PerkinElmer, Waltham, MA) were used in this study, as previously described . S. aureus SAP231 was grown in Brain Heart Infusion broth (BHI; Sigma–Aldrich, St. Louis, MO) and P. aeruginosa Xen41 was grown in Lysogeny Broth (LB; Sigma–Aldrich) respectively at 37°C overnight on shaker conditions set at 200 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They release the full antibiotic load and achieve high levels of antibiotics locally over sustained periods, leaving no residual foreign body that could act as a nidus for biofilm formation. We have previously studied the killing of biofilms of bioluminescent strains of P. aeruginosa (PA-Xen41) and S. aureus (SA-SAP231) grown on agar surfaces by a combination of vancomycin and tobramycin impregnated calcium sulfate beads for three days [38]. In this present study, we extended the incubation period to determine whether we could achieve complete eradication of biofilm bacteria adjacent to the beads, including resistant phenotypes that develop in the presence of antibiotics.…”
Section: Introductionmentioning
confidence: 98%
“…The main drawback of antibiotics‐loaded PMMA is the superfluous drugs at the initial releasing stage, which thus contributed to a deficient concentration for therapeutics at the later stage [5,6]. Due to the nonbiodegradable property of PMMA, the continuous reduction of antibiotics released by PMMA may result in proliferation of bacteria at the local sites and forming biofilms, which would be beneficial for the production of resistant bacteria and the recurrence of infection [7,8].…”
mentioning
confidence: 99%